Use of remifentanil to reduce propofol injection pain and the required propofol dose in upper digestive tract endoscopy diagnostic tests - Uliana,Gustavo Nadal (2015)
BACKGROUND AND OBJECTIVES: The introduction of propofol (2,6-diisopropylphenol) as a sedative agent has transformed the area of sedation for endoscopic procedures. However, a major drawback of sedation with the use of propofol is its high incidence of injection pain. The most widely used technique in reducing propofol injection pain is through the association of other drugs. The aim of this study was to evaluate the effect of remifentanil-propofol combination on the incidence of propofol injection pain and its influence on the total dose of propofol required for sedation in upper digestive tract endoscopy (UDE) diagnostic tests. METHOD: One hundred and five patients undergoing upper digestive tract endoscopy were evaluated and randomly divided into 3 groups of 35 patients each. The Control Group received propofol alone; Study-group 1 received remifentanil at a fixed dose of 0.2 mg/kg combined with propofol; Study-group 2 received remifentanil at a fixed dose of 0.3 mg/kg combined with propofol. The incidence of propofol injection pain and the total dose of propofol required for the test were evaluated. The sample was very similar regarding age, weight, height, sex, and physical status. Statistical analysis was performed according to the nature of the evaluated data. Student'st-test was used to compare the mean of age, weight, height (cm), and dose (mg/kg) variables between groups. The χ2 test was used to compare sex, physical status, and propofol injection pain between groups. The significance level was a < 0.05. RESULTS: There was significant statistical difference between the study groups and the control group regarding the parameters of propofol injection pain and total dose of propofol (mg/kg) used. However, there were no statistical differences between the two study groups for these parameters. CONCLUSION: We conclude that the use of remifentanil at doses of 0.2 mg/kg and 0.3 mg/kg was effective for reducing both the propofol injection pain and the total dose of propofol used.